“WHITE AND BLACK IN ENGLISH: A COGNITIVE-SEMANTIC AND SYMBOLIC ANALYSIS” - Djumamuratova, Gulbakhar (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This article investigates the semantic, idiomatic, and symbolic uses of the white and black color terms in English. Adopting a cognitive-semantic and discourse-analytic approach, it examines how white and black function as metaphors, moral symbols, and evaluative devices in modern English. The study draws on psycholinguistic experiments, corpora of idioms, and literary examples. It finds that while white and black maintain a strong dual opposition in morality and aesthetics, their use is nuanced by context, allowing for ambivalence, reversal, or metaphorical extension.